PENERAPAN KEBIJAKAN PUBLIK DALAM UPAYA PENCEGAHAN PERTAMBANGAN ILLEGAL BAHAN GALIAN C (STUDI KASUS DI KECAMATAN BATAUGA KABUPATEN BUTON SELATAN): Public Policy Implementation In Efforts To Prevent Illegal Mining Of Mineral C (Case Study In Batauga District, Buton South Regency) - Endrawati, Hesti (Restorica: Jurnal Ilmiah Ilmu Administrasi Negara dan Ilmu Komunikasi, 2023)
Indonesia is known as a producer of abundant natural resources, one of which is mining materials such as sand, gold, copper, nickel, coal, tin. The existence of a wealth of mining materials in Indonesia raises polemics regarding illegal mining activities or mining without permits. Batauga District is one of the areas in South Buton Regency which has the potential for mining C in the form of a sand mine which can produce in quite large quantities. With the potential for sand mining in Batauga District, it has negative impacts related to environmental preservation. Therefore, this study aims to analyze the application of public policy in preventing the mining of mineral C in Batauga District, South Buton Regency. The method used in this research is qualitative by using literature study techniques. The findings from this research are that the implementation of mineral C mining policies in Batauga District in preventing illegal mining is still low, both in terms of organizational activities, interpretation and application. solutions that can be applied to overcome the problem of illegal mining in Batauga District, include: the reformulation of regulations, the government making repressive efforts, improving bureaucracy, and the Government conducting outreach to the community.